Artificial Intelligence Integration in Academic Writing: Insights from the University of Duhok - Abdulah, Deldar M.; Zaman, Burhan A.; Mustafa, Zuhair R.; Hassan, Lokman H. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2024)
This study investigates the use of artificial intelligence (AI) technologies among academics at the University of Duhok (UoD), focusing on their perspectives, preferences, and intentions toward integrating AI within academic and research environments. A survey was conducted through Google Forms, targeting postgraduate students, recent alumni (since 2020), and faculty members of UoD in the Kurdistan region of Iraq. A total of 674 participants, aged 22–70 years, responded. The findings indicate that only 36.94% had employed AI technologies. Among AI users (n = 249), primary sources of information were friends or colleagues (46.59%) and social media (35.74%). Younger individuals and those holding master’s degrees exhibited a stronger tendency toward AI usage (p < 0.0001), whereas gender and academic discipline had minimal influence. ChatGPT was the most widely used tool (70.68%), followed by Quill Bot (42.17%), Grammarly (34.94%), and Google Bard (29.32%). The main AI applications were text paraphrasing (33.73%) and information retrieval (15.26%). Notably, 47.58% of respondents recommended AI for various academic tasks, including scientific research and idea generation. In conclusion, the study shows that only one-third of UoD faculty members utilize AI, predominantly for text paraphrasing. Nearly half of the participants suggested the adoption of AI by postgraduate students and academic staff.